The Last Council: Amulet #4 - Kibuishi, Kazu, 1978-; Caffoe, Jason (New York, NY : Graphix, an imprint of Scholastic, 2011)
Upon arrival in Cielis, Emily is escorted to the Academy where she is expected to compete for a spot on the Guardian Council, but as the candidate pool grows smaller, a secret that threatens everything Emily is fighting for is slowly revealed.
Chiefly illustrations.
Keywords: Secrets -- Fiction; Fantasy; Siblings -- Fiction; Graphic novels